Functioning of the Immune System in Children, After Surgical Correction of Congenital Heart Defects - Kurbanovna, Sadulloeva Iroda (European Journal of Life Safety and Stability (2660-9630), 2021)
It is reported that the overall prevalence of CHD at birth has increased significantly over the past century, reaching a stable estimate of 9 cases per 1,000 live births over the past 15 years. The results of scientific works have shown that the problem of the consequences of induced thymectomy for improving surgical access to the heart during its surgical correction in children in the aspect of the formation of immunopathological conditions remains relevant. In children with CHD, it is important to conduct immunological studies to assess the severity of the pathological process, severity, course, and prognosis of outcomes. The study aimed to study the functioning of the immune system in children who underwent surgical treatment of congenital heart defects Materials and methods: 58 children with CHD were examined based on the Bukhara Regional Children's Multidisciplinary Medical Center (BRChMMC) in the cityof Bukhara, whose mothers were excluded from immunological diseases. They were divided into 2 groups: the first group-30 children with ventricular septal defect(VSD) after surgery in the age the second group - 28 children with Fallot's Tetralogy(TF) after surgery in the age related groups. Indicators of cellular and humoral immunity, cytokine (IL-10, TNF-α) status were studied. Results and discussion: A 2.4-fold increase in the relative content of NK cells was found (p<0,01)in VSD and TF, there is a persistent continuation of T-lymphocyte deficiency and a compensatory increase in suppressor (CDCD8) and, especially, CD-killers (CD16) activity. A dynamic study of the concentrations of immunoglobulins G, A, and M showed a decrease in the synthesis of Ig A in all types of CHD after the surgical period. A 4-fold increase in the titer of IL-10 and TNF-α was found in VSD and TF after surgery. This means that CHD in the postoperative period is characterized by a multidirectional immunomodulatory effect of TNF-α. Conclusions: Thus, surgical correction of CHD with sternotomy (partial or complete removal of the thymus) later leads to a decrease in innate and adaptive immunity.